The Dutch Republic in the seventeenth century the golden age - Prak, Maarten 1955- (Cambridge University Press, 2005)
The Dutch are 'the envy of some, the fear of others, and the wonder of all their neighbours'. So wrote the English ambassador to the Dutch Republic, Sir William Temple, in 1673. Maarten Prak offers a lively and innovative history of the Dutch Golden Age, charting its political, social, economic and cultural history through chapters that range from the introduction of the tulip to the experiences of immigrants and Jews in Dutch society, the paintings of Vermeer and Rembrandt, and the ideas of Spinoza. He places the Dutch 'miracle' in a European context, examining the Golden Age both as the product of its own past and as the harbinger of a more modern, industrialised and enlightened society. A fascinating and accessible study, this 2005 book will prove invaluable reading to anyone interested in Dutch history